2014
DOI: 10.1186/1471-2334-14-383
|View full text |Cite
|
Sign up to set email alerts
|

Agreement between QuantiFERON®-TB Gold In-Tube and the tuberculin skin test and predictors of positive test results in Warao Amerindian pediatric tuberculosis contacts

Abstract: BackgroundInterferon-gamma release assays have emerged as a more specific alternative to the tuberculin skin test (TST) for detection of tuberculosis (TB) infection, especially in Bacille Calmette-Guérin (BCG) vaccinated people. We determined the prevalence of Mycobacterium tuberculosis infection by TST and QuantiFERON®-TB Gold In-Tube (QFT-GIT) and assessed agreement between the two test methods and factors associated with positivity in either test in Warao Amerindian children in Venezuela. Furthermore, progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 49 publications
0
11
1
Order By: Relevance
“…Results have been conflicting at times, with some studies showing comparable sensitivity and specificity to TST, whereas others found higher or lower sensitivity. 3,[26][27][28][29][30][31][32] Rates of indeterminate QFT tests have been higher in young children than in adults; 26,[33][34][35][36] although in this study, we noted a low rate of indeterminate tests (0·4% of all tests).…”
Section: Discussionmentioning
confidence: 54%
“…Results have been conflicting at times, with some studies showing comparable sensitivity and specificity to TST, whereas others found higher or lower sensitivity. 3,[26][27][28][29][30][31][32] Rates of indeterminate QFT tests have been higher in young children than in adults; 26,[33][34][35][36] although in this study, we noted a low rate of indeterminate tests (0·4% of all tests).…”
Section: Discussionmentioning
confidence: 54%
“…Many of these 59 studies did not have the primary aim of assessing diagnostic accuracy. Many recorded few cases of active TB (often < 10) 22,[25][26][27][29][30][31][32][33][35][36][37][38]40,[42][43][44][45]47,48,50,51,[56][57][58][59][62][63][64][65][67][68][69][70][71][72][73][74][75]77,78 and/or were restricted to groups such as patients infected with HIV, 9,28,29,36,49,51,56,60,65,…”
Section: Diagnostic Performance Of Interferon Gamma Release Assays Fomentioning
confidence: 99%
“…Of these, five assessed both IGRAs and TST. 23,52,56,62,72 Except when noted, these studies did not include treatment for LTBI. In this subset of studies, estimates of the PPVs ranged from < 1% to 17%, whereas the NPV was ≥ 97%.…”
Section: Diagnostic Performance Of Interferon Gamma Release Assays Fomentioning
confidence: 99%
See 1 more Smart Citation
“…The low IFNG expression levels detected may be correlated with the present findings in relation to QFT-IT assays; among the LTBI indigenous individuals tested, only 4 of were QFT-IT+. In this context, the value of the QFT-IT as an adjunct in diagnosing latent infection in Warao individuals may be limited: in Warao children for whom both TST and QFT-IT results are available, the proportion of children with a positive TST was high compared with those with a positive QFT-IT 22 . The latter correlates with the present results; therefore, replacement of the TST by QFT-IT for detection of M. tuberculosis infection is not recommended in this indigenous population.…”
Section: Discussionmentioning
confidence: 99%